Implementing a strategy for on-chip detection of cell-free DNA fragments using GMR sensors: A translational application in cancer diagnostics using ALU elements. Issue 1 (27th November 2015) - Dias, T. M.; Cardoso, F. A.; Martins, S. A. M.; Martins, V. C.; Cardoso, S.; Gaspar, J. F.; Monteiro, G.; Freitas, P. P.
Abstract : Optimization of a strategy for the detection of cell-free DNA using an array of magnetoresistive (MR) sensors integrated in a portable readout platform. Abstract : Cell-free DNA (cfDNA) is foreseen as a promising source for liquid biopsies in cancer diagnostics. Despite its promise, methods available for its evaluation lack in robustness or, in the case of next-generation sequencing (NGS), are extremely sensitive but overly complex for routine operation. In contrast to NGS, integrated lab-on-chip devices offer advantages particularly in terms of automation, cost and speed. These devices, however, have rarely demonstrated the detection of biologically relevant DNA fragments originating from blood. To this end, we present a strategy for the magnetic labeling and detection of cfDNA fragments, using an array of 30 magnetoresistive (MR) sensors integrated in a portable biochip platform. As a proof-of-concept, we selected the fragments ALU115 and ALU247, recently identified as promising cancer targets in cfDNA integrity assessment. This work reveals a rational optimization of the DNA probes design and density at the surface which allowed achieving specific target detection and increased inhibition of unspecific interactions, without the need for blocking agents. The developed strategy is adaptable for the detection of mutations, homologous or truncated sequences such as the case of ALU115 and ALU247, sequences that share great similarity. Upon optimization, the MR sensors detected a concentration of the ALU elements within the picomolar range, showing potential for cfDNA analysis in cancer diagnostics.